Potentials of typical plant species from rewetted fenlands for the supply of strategic elements - Karina Michalska; Monika Heiermann; Carsten Lühr; Björn Meermann; Ralf Pecenka; Andreas Schulz; Nicole Langhammer; Susanne Theuerl; Annette Prochnow (Scientific Reports)
Abstract Rewetting of peatlands requires the development of new biomass utilization pathways. The supply of strategic elements with key importance for the development of priority technologies, such as germanium (Ge), silicon (Si) and rare earth elements, from fenland plants is one option. To provide a first estimation of the potential, concentrations of strategic elements were determined in nine biomass samples covering typical fenland vegetation in northeast Germany. Subsequently, a simplified estimation of potential revenue from strategic element recovery was made. The analysed plant species can be classified as high or intermediate Si plant accumulators with highest contents of more than 16.0 g Si kg−1 dry mass (DM) in sedges and common reeds. Ge concentrations were lower with reed canary grass containing the highest amounts of 465.3 µg Ge kg−1 DM. Simultaneous acquisition of Ge and Si could provide higher total element yields and revenues of up to 500 $ ha−1. In contrast, the potentials for supplying rare earth elements appeared to be very low, with common reed containing the highest sum of rare earth elements of 437.4 µg kg−1 DM. Biomass from rewetted fenlands is capable of accumulating strategic elements. More knowledge is required to understand the factors affecting their accumulation.